SAT0151 Diagnostic criteria of osteoporosis in patients with ra. (1st June 2001) - Sohen, S; Kamiya, M; Ueno, M; Kikuchi, H; Nonaka, T; Hamanishi, T
Abstract : Background: We reported that generalised bone loss was observed in rheumatoid arthritis (RA), especially in post menopausal patients and closely correlate with the activity of RA. On the other hand, glucocorticoids are used in the treatment of active patients with RA. Osteoporosis and related fractures are one of the most serious adverse effects of glucocorticoids. Objectives: Recommendations for the prevention and treatment of glucocorticoid-induced osteoporosis were proposed by American College of Rheumatology and UK Consensus Group. On the other hand, the diagnosis of osteoporosis in patients with RA was usually made by the diagnostic criteria of primary osteoporosis. The purpose of the present study was to clarify the validity of using the diagnostic criteria of primary osteoporosis for the diagnosis of osteoporosis in RA. Methods: The cutoff values were defined as the value by which the subjects with spine fracture were discriminated from those without spine fracture efficiently in terms of sensitivity and specificity. The subjects and measurement of bone mineral density (BMD) were follows: number of subjects; 256 (47 with vertebral fracture, 219 without vertebral fracture), age of subjects (mean ± SD); fracture group 64.2 ± 9.0 years, non fracture group 59.8 ± 10.9 years, measured site (type of machine); lumbar spine (QDR). Patients treated with glucocorticoid were follows: number of subjects; 103(29 with vertebral fracture, 74 without vertebral fracture), Age of subjects (mean ± SD); fracture group 65.1 ± 12.5 years, non fracture group 54.2 ± 13.6 years. Results: The cutoff value of all patients with RA was 0.711 g/cm 2 (T score: -2.6, % of the young adult mean (%YAM): 70%). This value was almost same as the cutoff value (BMD: 0.708, %YAM:70%) of osteoporosis proposed by the Japanese diagnostic criteria of primary osteoporosis and as the cutoff value (T score below -2.5) of osteoporosis proposed by the WHO diagnostic criteria. On the other hand, the cutoff value in the patients treated with daily doses of 7.5 mg or more prednisolone was 0.812 g/cm 2 (T score: -1.7, %YAM: 80%). This value was almost same as the value of osteopenia by the Japanese diagnostic criteria (%YAM below 80%) and by the WHO diagnostic criteria (T score below -1.0). Conclusion: These results supported the validity of using the diagnostic criteria of primary osteoporosis for the diagnosis of osteoporosis in patients with RA. But, in patients treated with daily doses of 7.5 mg or more prednisolone, we have to start the treatment for preventing bone loss, if the patients are diagnosed for osteopenia using the diagnostic criteria of primary osteoporosis.